Diksi dalam Syair Dero Tradisional “Kajian Stilistika” - Siti Aminah Lapangandong; Moh. Tahir; Yunidar Yunidar; Ruhaliah Ruhaliah (SAWERIGADING, 2026)
The research aims to describe the classification of diction and to explain the linguistic, social, spiritual, and philosophical meanings reflected in Dero poetry. This study employed a stylistic approach using a descriptive qualitative method. The data consisted of 30 Dero poetry texts collected through interviews, observation, documentation, and note-taking from Pamona community informants. Data were analyzed through the stages of data reduction, classification, interpretation, and conclusion drawing. The findings show that the diction in Dero poetry can be classified into several categories, namely religious diction, kinship and brotherhood, nature and agriculture, romantic and affectionate expression, praise and respect, advice and wisdom, struggle and life spirit, sorrow and separation, customs and rituals, as well as symbolic and metaphorical diction. These word choices contain denotative, connotative, and philosophical meanings that reflect the Pamona worldview concerning the relationship between humans, God, fellow human beings, nature, and customary values. In addition, Dero poetry functions as a medium of moral education, reinforcement of social solidarity, emotional expression, and a marker of local cultural identity. Therefore, Dero poetry represents a cultural heritage that integrates language, art, and the life values of the Pamona people. AbstrakPenelitian ini bertujuan mendeskripsikan klasifikasi ragam diksi serta menjelaskan makna linguistik, sosial, spiritual, dan filosofis yang tercermin dalam syair Dero. Penelitian menggunakan pendekatan stilistika dengan metode deskriptif kualitatif. Data penelitian berupa 30 teks syair Dero yang diperoleh melalui wawancara, observasi, dokumentasi, dan pencatatan dari informan masyarakat Pamona. Analisis data dilakukan melalui tahap reduksi data, klasifikasi, interpretasi, dan penarikan simpulan. Hasil penelitian menunjukkan bahwa diksi dalam syair Dero terbagi ke dalam beberapa kategori, yaitu religius, kekerabatan dan persaudaraan, alam dan pertanian, romantis dan kasih sayang, pujian dan penghormatan, nasihat dan kebijaksanaan, perjuangan dan semangat hidup, kesedihan dan perpisahan, adat dan upacara, serta simbolik dan metaforis. Diksi-diksi tersebut mengandung makna denotatif, konotatif, dan filosofis yang mencerminkan pandangan hidup masyarakat Pamona tentang hubungan manusia dengan Tuhan, sesama, alam, dan adat. Selain itu, syair Dero berfungsi sebagai media pendidikan moral, penguat solidaritas sosial, ekspresi emosional, dan penanda identitas budaya lokal. Dengan demikian, syair Dero merupakan warisan budaya yang memadukan bahasa, seni, dan nilai kehidupan masyarakat Pamona.